2021
DOI: 10.1093/jpepsy/jsab130
|View full text |Cite
|
Sign up to set email alerts
|

Worries and Benefit Finding in Cancer Survivors and Parents: A Longitudinal Study

Abstract: Objective The interplay and longitudinal associations between positive and negative illness-related experiences in childhood cancer survivors and their families remain unclear. Therefore, benefit finding, cancer-related worries, depressive symptoms, and life satisfaction were prospectively investigated in childhood cancer survivors and parents. Directionality of effects and interactions between benefit finding and cancer-related worries in predicting general well-being were examined. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 38 publications
0
33
0
Order By: Relevance
“…Additionally, participants in the intervention group had the sessions on stress management, including coping, and learned, practiced, and shared their stress management. As earlier studies suggested [ 15 , 37 ], improved stress management could contribute to better subjective well-being. In addition, according to the social cognitive processing theory, the disclosure of one’s own experiences can enable a coherent restructuring of tough memories into existing schemas, which leads to stress relief and improved health [ 19 ].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Additionally, participants in the intervention group had the sessions on stress management, including coping, and learned, practiced, and shared their stress management. As earlier studies suggested [ 15 , 37 ], improved stress management could contribute to better subjective well-being. In addition, according to the social cognitive processing theory, the disclosure of one’s own experiences can enable a coherent restructuring of tough memories into existing schemas, which leads to stress relief and improved health [ 19 ].…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies suggested that the experience of benefit finding would contribute to further progress in personal recovery among people with mental illness. Particularly, enhancing benefit finding may lead to higher personal recovery as well as subjective well-being and better mental health [ 7 , 12 , 13 , 14 , 15 ]. Therefore, many studies to date have emphasized the significance to facilitate benefit finding, including for people with mental illness [ 8 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The current study was part of a larger cohort study, the LInC‐study: Longitudinal Identity study in CCS, approved by the Medical Ethics Committee of KU Leuven (Prikken et al. (2022) 28 ).…”
Section: Methodsmentioning
confidence: 99%
“…Full details on all included questionnaires in the LInC‐study were described previously (Prikken et al. (2022) 28 ). To examine our objective, we focused on the assessment of fear of cancer recurrence, post‐traumatic stress, resilience and fatigue at two timepoints with a 1‐year interval (T1 and T2).…”
Section: Methodsmentioning
confidence: 99%
“…Completion of childhood cancer treatment is a period of vulnerability for parents 1,2 with most actively involved in the child's physical and psychosocial care related to the cancer years after treatment. After treatment, many parents adequately adjust and cope successfully with the transition, 2,3 reporting positive changes such as posttraumatic growth 4 and benefit finding (e.g., finding purpose in life and developing helpful coping strategies) 5 . Despite this, anxiety, depression, post‐traumatic stress (PTSS), 2 , 6 8 productivity losses, 9 and restrictions on daily life 10 are reported by a subgroup of parents.…”
Section: Introductionmentioning
confidence: 99%